VET research: where have we been? A qualitative content analysis of an Australian vocational education journal, 1993 to 2019. (1st September 2020) - Clayton, Berwyn; Harris, Roger
ABSTRACT: Academic journals communicate research findings, share knowledge and stimulate debate. They are the representative academic 'voice' for a discipline, reflecting its knowledge base. This paper examines all 350 articles published in the International Journal of Training Research from 1993 to 2019 to highlight significant trends over 27 years. It analyses the 462 authors, the article types and methodological characteristics, and their key themes and sub-themes. Analysis of authorship over time reveals rises in the proportions of females publishing, of international contributors from 30 different countries, of contributors affiliated with universities and of multiple authorship. Two-thirds of the articles were qualitative research or expository. Key themes were on political, organisational and structural change and on students, followed by vocational knowledge, learning and instruction, and vocational teachers. Studying the themes and sub-themes over time showed how their relative popularity in research has tended to parallel policy developments in the VET sector.